Implementation of Digital Marketing Strategy for Improving UMKM Website Promotion (Case Study: Rumah Mesin) - Choiruddin; Tikaridha Hardiani (Procedia of Engineering and Life Science, 2021)
The advancement of information technology is increasingly rapid, so search engines are the main choice as a medium for marketing products and services, and also for increasing the popularity of a website's existence. The main problem faced by the company CV. The machine house is competition in the world of machinery that is so fierce that the internet is needed to help it compete with the company's competitors. The way this is done is by promoting using SEO (Search Engine Optimization) Digital Marketing techniques. This research was carried out on a website where initially the techniques of SEO were just not optimal, then by applying the SEO on Page method such as keyword optimization in the title tag, content, meta keywords, meta description, at this stage several tests were also carried out as benchmarks for the success of implementing SEO techniques. The results of the application of SEO techniques are able to increase the SERP (Search Engine Results Page) of the website in search engines and successfully indexed by Google to be on the first page of page 9 in the second month.